INFLUENCE OF THE TRADITIONAL FEMININE ROLE ON THE ANXIETY SYMPTOMS IN A SAMPLE OF ADULTS WOMEN - Pérez Blasco, Josefa; Serra Desfilis, Emilia (Anales de Psicología / Annals of Psychology)
In this paper we present the results of an study which objective is analysing the influence that several aspects of role traditional feminine have in the anxious syntomatology in adult women. This aspects are to be housewife, the Feminity, and the Belives Traditional toward the Woman’s Role. The same is constituted for 401 (25-45 yr) who were evaluated with the folowing instruments: Personal Attributes Questionnaire (PAQ) (Spence & Helmrich, 1978), the Belives Toward Women Role Scale (Pérez-Blasco y Serra, 1994) and the Anxiety Inventory (Zung, 1971). The results suggest, in agreement with other investigations, the existence of correlation between feminity and anxiety and between tradicionality and anxiety, but no between to be housewife and anxiety.